Etos Kerja Kepala Sekolah Menengah Pertama Islam Al Istiqomah Kecamatan Baleendah Kabupaten Bandung Jawa Barat - Aripin, Zaenal; Agus Sujarwo; Dewi Yanti (UNISAN JURNAL, 2025)
This study aims to describe the work ethic of the principal of SMP Islam Al Istiqomah Baleendah in the 2025/2026 Academic Year. The research focuses on aspects of discipline, responsibility, integrity, professionalism, and leadership performance that influence the overall quality of school management. This study employs a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings reveal that the principal demonstrates a strong work ethic reflected through consistent discipline, commitment to improving educational quality, effective communication with school stakeholders, and the ability to manage school programs systematically. Furthermore, the principal successfully motivates teachers and staff by providing exemplary leadership, continuous guidance, and recognition. The study concludes that the principal’s work ethic significantly contributes to creating a productive and harmonious school environment oriented toward improving learning quality. These findings are expected to serve as a reference for strengthening effective school leadership practices.